Effects of Aging on Seedling Emergence and Establishment of Barley under Soil Moisture Stress - NEZAR H. SAMARAH,; SALMAN AL-KDFAHI, (Seed Research, 2026)
Early establishment and growth of barley is essential to achieve optimum yield in the semi-arid Mediterranean region, where soil moisture stress is common at planting time. Seed aging may reduce seedling emergence and establishment of barley under soil moisture stress. Seeds of two barley cultivars, ACSAD 176 and Rum, were subjected to aging at 42°C and 100% relative humidity for 0, 2, 4, 6, 8, or 10 days. Seed quality, as estimated by standard germination test, germination rate index, and seedling dry weight, was evaluated for the aged seeds. In a greenhouse experiment, aged seeds were grown in soil maintained at 10, 30, 50, 70, and 90% of field capacity (FC) to evaluate seedling emergence, emergence rate index (ERI), and seedling dry weight (SDW). Seedling emergence of aged seeds was further evaluated at two field locations, characterized by low and high annual rainfall (Jordan University of Science and Technology (JUST) and Jomha, respectively). Aging treatments reduced seed germination, germination rate index (GRI), and seedling dry weight. Seed aging reduced seedling dry weight, but this reduction was higher in Rum than ACSAD 176. In the greenhouse experiment, aged seeds had lower seedling emergence, ERI, and SDW than those of un-aged seeds. The ability of seeds to emerge under moisture stress (10 and 90% FC) decreased as seed aging increased. Emergence rate index was more sensitive to moisture stress than emergence percentage and SDW. In the field experiment, aged seeds (2-, 4-, and 6-day) had lower emergence at the drier location (JUST) than that at Jomha. These results indicate that aged seeds should not be planted, where moisture stress is common at planting time.